Analysis of New Synthetic Drugs by Ion Mobility Time-of-Flight Mass Spectrometry. Issue 2 (April 2014) - Sysoev, Alexey A.; Poteshin, Sergey S.; Chernyshev, Denis M.; Karpov, Alexander V.; Tuzkov, Yuriy B.; Kyzmin, Vyacheslav V.; Sysoev, Alexander A.
Characteristic ion mobility mass spectrometry data, reduced mobility, and limits of detection (signal-to-noise ratio = 3) were determined for six synthetic drugs and cocaine by ion mobility time-of-flight mass spectrometry (IM-TOF-MS) with electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI). The studied synthetic illicit drugs recently appeared on the recreational drug market as designer drugs and were methylone, 4-MEC (4′-methylethcathinone), 3, 4-MDPV (3, 4-methylenedioxypyrovalerone), JWH-210 [4-ethylnaphthalen-1-yl-(1-pentylindol-3-yl)methanone], JWH-250 [2-(2-methoxyphenyl)-1-(1-pentyl-1H-indol-3-yl)ethanone], and JWH-203 [1-pentyl-3-(2′-chlorophenylacetyl) indole]. Absolute reduced mobilities in nitrogen were 1.35, 1.28, 1.41, 1.30, 1.18, 0.98, 1.09, and 1.07 cm 2 V −1 s −1, for methylone [M–H] +, methylone [M+H] +, 4-MEC [M–H] +, 4-MEC [M+H] +, 3, 4-MDPV [M+H] +, JWH-210 [M+H] +, JWH-250 [M+H] +, and JWH-203 [M+H] +, respectively. Selected illicit drugs are easily identified by IM-TOF-MS during a 100 s analysis. Relative limits of detection ranged from 4 to 400 nM are demonstrated for these compounds. Such relative limits of detection correspond to 14 pg to 2 ng absolute limits of detection. Better detection limits are obtained in APCI mode for all the illicit drugs except cocaine. ESI mode was found to be preferable for the IM-TOF-MS detection of cocaine at trace levels. A single sample analysis is completed in an order of magnitude less time than that for conventional liquid chromatography/mass spectrometry approach. The application allows one to consider IM-TOF-MS as a good candidate for a method to determine quickly the recently surfaced designer drugs marketed on the internet as "bath salts, " "spice, " and "herbal blends".